Incorporation CdS with ZnS as Composite and Using in Photo-Decolorization of Congo Red Dye - Faten Hadi Fakhri; Luma Majeed Ahmed (Universitas Gadjah Mada, 2019)
The aim of this manuscript was to modify the ZnS surface by incorporating with CdS photocatalyst. This manner led to depressing the recombination process and increasing the activity. The X-ray Powder Diffraction (XRD) data were proved that the CdS incorporated with ZnS and formed ZnS-CdS nanocomposite by observing new peaks at 26.92, 28.62, 30.52, and 47.26°. Based on the Atomic Force Microscopy (AFM) analysis and Tauc equation, the particle sizes for all samples were raised with decreased the band gap values. The activation energy for decolorization of Congo red with the using ZnS is found to be more than that value for the using prepared ZnS-CdS composite. The percentage of efficiency was found to be increased with modified the ZnS surface.